From framing to emotion: evolving narratives in Ibero-American political mediatization (2008–2019) - Ramírez-Salina, Carlos Alberto; Jiménez-Barbosa, Wilson Giovanni; Cala Vitery, Favio (Frontiers in Communication, 2025)
This review examines the relationship between media and politics in the Ibero-American context during the decade preceding the COVID-19 pandemic (2008–2019). Its primary objective is to identify the dominant research themes and prevailing methodological approaches in order to contribute to broader theoretical reflections on the evolution of political communication in the region. Based on the PRISMA-ScR framework, a sample of 32 publications was identified and selected for analysis. The findings reveal a clear predominance of qualitative studies, particularly those grounded in framing theory and discourse analysis. These works document how the rise of digital platforms, especially Twitter and Facebook, reshaped political communication by emphasizing emotionality, personalization, and media spectacle. The review also highlights the hybrid interaction between traditional and digital media, as well as the role of media narratives in shaping public opinion and institutional trust. In contrasting these findings with developments after 2019, the review identifies the growing impact of big data, algorithmic amplification, and AI-driven microtargeting as key factors reconfiguring political discourse. These dynamics expose critical research gaps and point to the need for methodological innovation and theoretical renewal.